The Nature of Parental Engagement at an Online Charter High School - Borup, Jered; Stevens, Mark A.; Hasler Waters, Lisa (Online Learning, 2015)
As enrollments in cyber charter schools grow, it becomes increasingly important to understand how parents engage in their students’ learning. Researchers have hypothesized that parental engagement is even more critical when online students learn from home, but few researchers have examined parents’ engagement behavior–especially parents of adolescent learners. In this case study we addressed this gap using parent and student interviews at a full-time online charter school. Our analysis of 19 interviews with 9 parents and 10 interviews with 10 students identified five primary types of parental engagement within this setting: (1) nurturing relationships and interactions, (2) advising and mentoring, (3) organizing, (4) monitoring and motivating student engagement, and (5) instructing. We also identified obstacles to effective parental engagement, and in this paper we discuss how programs can work with parents to foster more collaborative relationships.